A Case of Iatrogenic Cushing’s Syndrome - Del Toro Diez, Andrea (J Endocr Soc, 2021)
Cushing’s syndrome (CS) is considered a rare disease. The most common cause is the exogenous use of glucocorticoids (GCs), which are often given within a controlled medical setting, but their factitious use is rare. Factitious CS is more common in females, young patients, those with psychiatric disorders, and those with contacts within the medical field. The diagnosis of CS is challenging because some features are non-specific and commonly present in the general population, such as obesity, depression, diabetes, hypertension (HTN), and low bone mineral density (BMD). A high suspicion is warranted. We present the case of a 47-year-old man with HTN, obesity, dyslipidemia, obstructive sleep apnea, and low BMD who complained of increased appetite, significant weight gain, fatigue, sleepiness, muscle weakness, and occasional facial flushing. Medications include Hydrochlorothiazide, Furosemide, Losartan, Atorvastatin, and Teriparatide. Vital signs were normal and body mass index was 41.9 kg/m(2). He had a round face, central obesity, and wide purple striae in his abdomen. Dual-energy X-ray absorptiometry scan showed low BMD at spine. Laboratories revealed a glycated hemoglobin of 6.1%, late-night salivary cortisol of <0.03 mcg/dL, 24-hour urine free cortisol of 22.5 mcg/24hr, morning cortisol of 0.01 ug/mL, ACTH 23.5pg/mL, and dehydroepiandrosterone sulfate (DHEA-S) 35 mcg/dL. Our patient persistently denied use of exogenous GCs, but a urine synthetic GC screen disclosed a positive result for dexamethasone; levels at 1.1 mcg/dL. After an exhaustive conversation, our patient confessed to using over-the-counter dexamethasone 4mg to treat occasional muscle aches. ACTH is usually suppressed in factitious CS, but this was not our patient’s case, giving the appearance of ACTH-dependent hypercortisolism. This can lead to unnecessary diagnostic and therapeutic approaches. An unsuppressed ACTH could be due to an unreliable ACTH immunoassay or intermittent, instead of continuous, ingestion of GCs. A suppressed DHEA-S level, as seen in our patient, may provide the clue to exogenous GC use as the cause of CS. Our case is also rare because our patient is male, older, and not related to the medical field. Hypercortisolism must be detected and treated early due to its high morbidity and mortality. Several features may be reversed with treatment. The possibility of hypothalamic-pituitary-adrenal (HPA) axis suppression due to prolonged use of GCs, resulting in adrenal insufficiency (AI) should be considered. The prevalence of GC-induced AI ranges from 14–63%, with the highest risk in those with Cushingoid features and those receiving a dose equivalent to prednisone 20mg daily for more than three weeks. Sudden withdrawal of GCs should be avoided to prevent adrenal crisis. A tapering regimen should be adopted with subsequent biochemical testing of the HPA axis once GCs have been reduced to a physiologic dose.